Santri Inclusivism and Humanism in Islamic Law: Advancing Religious Tolerance and Social Welfare for Minority Communities - Akhris Fuadatis Sholikha; Sidik Fauji; M. Bintang Fadhlurrahman; Khafifatul Fian; Husni Mubarok (Khuluqiyya: Jurnal Kajian Hukum dan Studi Islam, 2026)
This study examines the inclusivism and humanism of santri (Islamic boarding school students) from the perspective of Islamic law and their contribution to promoting religious tolerance and social welfare for minority communities. Employing a qualitative field research approach, the study collected primary data through interviews administered via Google Forms. A total of 114 respondents who met the predetermined criteria participated in the research. The findings reveal that 52.6% of respondents had received information regarding the importance of inclusivity, while all respondents (100%) demonstrated an understanding of humanistic values within their social environment. In terms of religious tolerance, 96.5% of the santri reported that they were able to accept differing opinions and perspectives among their peers, indicating a strong commitment to coexistence and mutual respect. Regarding social welfare, 10.5% of respondents stated that they were highly capable of fulfilling their basic needs, 79.8% considered themselves capable, 9.6% reported limitations in meeting those needs, and only 0.1% indicated complete inability to do so. These findings suggest that the majority of santri embody values of inclusivism, humanism, tolerance, and social well-being that are consistent with the principles of Islamic law, particularly justice, compassion, and social harmony. Consequently, santri have significant potential to contribute to the advancement of peaceful and inclusive pluralistic societies.